Validation and initial results of surveys exploring perspectives on risks and solutions for diagnostic and medication errors in primary care in Sweden - Rita Fernholm; Caroline Wachtler; Karolina Malm-Willadsen; Martin J. Holzmann; Axel C. Carlsson; Gunnar H. Nilsson; Karin Pukk Härenstam (Taylor & Francis Group, 2020)
Objective To (1) validate and (2) display initial results of surveys to health care professionals and patients on the importance and mitigation of specified risks for diagnostic and medication errors. Design For validation, psychometric properties were analysed by assessment of construct validity and internal consistency by factor analysis. Non-parametric analyses were used concerning areas of risk, and top ranking of solutions were reported descriptively. Setting Primary health care in Sweden. Participants Health care professionals (HCPs); including physicians, nurses and practice managers, as well as patients who had experienced diagnostic or medication errors. Main outcome measures Psychometric properties of the surveys. Median ratings for risks and top rankings of solutions for professionals and patients. Results There were 939 respondents to the HCP survey. Construct validity resulted in a model with four dimensions: Patient-provider level; Support systems for every day clinical work; Shared information and cooperation between different caregivers; Risks in the environment. Internal consistency was acceptable with Cronbach's α values above 0.7. Confirmatory factor analysis generally showed an acceptable fit. Initial results from the professionals showed the importance of continuity of care, a nationwide on-line medical platform and cooperation in transfer of care. The patient survey could not be validated because of low response rate. Conclusion The HCP survey showed some contradicting results regarding model fit and may be tentatively acceptable but validity needs further study. HCP survey answers indicated that relational continuity of care and a nationwide on-line medical platform are highly valued.Current awareness Health care professionals and patients are rather untapped sources of knowledge regarding patient safety in primary health care Main statements Validation is performed on a new survey capturing rating of risks and solutions. The validation of the health care professional survey is tentatively acceptable. Survey answers indicate that health care professionals' and patients' perspectives are complementary.